An overview of Wajda Tabassum’s Novels and Novelettes - Kallu, Parveen; Sahar, Nazia; Rahman, Muhammad (sourcecoder, 2024)
Wajida Tabassum has tried to prove that all the work of this world is not done by one man by describing the life of Riji(A character)extensively and deeply in her fitcions. And it is not enough for a person to take responsibility for everything. Every human being sent to this world has a role of his own. It is enough if he plays his role well. Riji took all the work and responsibilities of the world on his head. He also took on the tasks that were not his, that is, when his brother Javed became a doctor, he was going to get married, so now Raji’s responsibility was over. Now she too should have thought about her future and had to fill a supporter for the marriage, but after that taking the responsibility of bringing up and taking care of her brother’s children was an additional burden. Because of which she goes crazy and when she recovers, the water has gone over her head.